Ligand Activation of the Prokaryotic Pentameric Ligand-Gated Ion Channel ELIC - Zimmermann, Iwan; Dutzler, Raimund (PLOS Biology, 2011)
Author Summary Electrical signal transduction at chemical synapses of nerve and muscle cells is initiated by the binding of neurotransmitters to their receptors, which function as gated ion channels that open a selective ion conduction path in the ligand-bound state. The pentameric ligand-gated ion channels constitute a very important family of neurotransmitter receptors that includes, amongst others, the nicotinic acetylcholine receptor. While most pLGICs are expressed in higher eukaryotes, there are few family members found in bacteria. These bacterial channels share the overall structural features of the family and are thus expected to function by similar mechanisms, but although the channel from the bacteria Erwinia chrysanthemi has revealed first structural insight into the family at high resolution, its functional characterization was impossible since activating ligands were not known. In our study we have identified ligands activating ELIC and we have located their binding by X-ray crystallography. Ligand binding causes the transition into an open state, which, as in eukaryotic receptors, is only transient and which slowly inactivates in the presence of the ligand. By single channel analysis we found that, similar to the acetylcholine receptor, ELIC forms cation selective channels. With known ligands ELIC has become an important model system to study the general mechanisms of the family.